Public Policies and Private Savings and Investment in Sub-Saharan Africa : An Empirical Investigation - Ghura, Dhaneshwar; Hadjimichael, Michael (Washington, D.C. : International Monetary Fund, 1995)
This paper assesses empirically the role of public policies in stimulating private savings and investment in sub-Saharan African countries, based on data for the period 1986-92. The main findings of the analysis are as follows: (i) policies effective in stimulating private savings and investment include those that keep the rate of inflation low, reduce macroeconomic uncertainty, promote financial deepening, and lower the external debt burden; (ii) measures that promote structural reforms and reduce the budget deficit (without lowering government investment) help to raise private investment; and (iii) declines in government savings are only partially offset by increases in private savings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet